Design and characterization of a tri-band monopole antenna for multiband applications - Mohd Nor Azami, Mohd Adzimnuddin; Abd. Aziz, Mohamad Zoinol Abidin; Ja'afar, Abd Shukur (2024)
This study introduces a tri-band monopole antenna tailored for multiband applications. It is engineered to operate at 1.67 GHz, 2.15 GHz, and 2.64 GHz, achieving respective return loss values of -22.07 dB, -24.34 dB, and -20.50 dB. This performance is achieved through the incorporation of specialized inverted L-shaped stubs. The antenna showcases commendable gain and radiation patterns, affirming its efficacy for various wireless communication requirements demanding tri-band capability.